1995
DOI: 10.1111/j.1651-2227.1995.tb13602.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of dehydration in young children with acute watery diarrhoea: a case‐control study

Abstract: In a case-control study to understand the risk factors for development of life-threatening dehydration, a total of 379 children comprising 243 cases (moderate or severe dehydration) and 136 controls (non or mild dehydration) up to 2 years of age suffering from acute watery diarrhoea were studied. By univariate analysis, the presence of vibrios in stool, withdrawal of breast feeding during diarrhoea, not giving fluids, including oral rehydration solution (ORS), during diarrhoea, frequent purging ( > 8/day), vom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
1
7
2
2
Order By: Relevance
“…Monthly distribution of the cases admitted to the hospital with acute gastroenteritis and with rotavirus antigens detected in the stools. dehydration [14][15][16][17]. We found that most of our patients presented signs of dehydration, as expected in patients requiring hospital admission.…”
Section: Discussionmentioning
confidence: 48%
“…Monthly distribution of the cases admitted to the hospital with acute gastroenteritis and with rotavirus antigens detected in the stools. dehydration [14][15][16][17]. We found that most of our patients presented signs of dehydration, as expected in patients requiring hospital admission.…”
Section: Discussionmentioning
confidence: 48%
“…The following reached Delphi consensus agreement. Children presenting to hospital with acute gastroenteritis who are severely dehydrated should be admitted to hospital. Those children with mild–moderate dehydration should be observed in a hospital paediatric facility for a period of at least 6 hours to ensure successful rehydration (3–4 hours) and maintenance of hydration (2–3 hours). Those children at high risk of dehydration on the basis of young age (infants <6 months22 23 (III, C)), high frequency of watery stools (more than eight per 24 hours22 24 (III, C)) or vomits (more than four per 24 hours22 24 (III, C)) should be observed in a hospital paediatric facility for at least 4–6 hours to ensure adequate maintenance of hydration. Those children whose parents or carers are thought to be unable to manage the child's condition at home successfully should be admitted to hospital. …”
Section: The Guidelinementioning
confidence: 99%
“…Those children at high risk of dehydration on the basis of young age (infants <6 months22 23 (III, C)), high frequency of watery stools (more than eight per 24 hours22 24 (III, C)) or vomits (more than four per 24 hours22 24 (III, C)) should be observed in a hospital paediatric facility for at least 4–6 hours to ensure adequate maintenance of hydration.…”
Section: The Guidelinementioning
confidence: 99%
“…Des échelles cliniques d'évaluation de la déshydratation combinant plusieurs signes [14][15][16][17][18][19][20], et des scores de gravité des diarrhées aiguës ont été proposés [21][22][23][24]. Nombre de ces scores ont été élaborés pour des populations issues des pays en voie de développement [14,17,20] et n'ont pas été validés, notamment l'échelle OMS souvent utilisée [11]. Une revue systématique en langue anglaise, publiée en 2004 dans le JAMA [11], soulignait que l'apport des données de l'histoire clinique, de l'examen, et des tests biologiques était encore considéré comme mal évalué et non validé.…”
Section: Résuméunclassified
“…Dans les recommandations[3,17,38], le risque de déshydrata-tion augmente avec le jeune âge (< 6 mois), la fréquence des selles (> 8/j) et des vomissements (> 2/j[17,33] ou > 4/j[3]). Ces valeurs n'ont pas été validées dans des populations identiques à celles que nous traitons, car elles proviennent essentiellement d'une étude rétrospective réalisée en Inde, chez des enfants dénutris dont certains infectés par le choléra[17]. De plus elle n'utilise pas le critère gold standard d'évalua-tion de la déshydratation.…”
unclassified